DO TERRITÓRIO USADO À MULTITERRITORIALIDADE: REFLEXÕES SOBRE O LAZER E O TURISMO EM SEGUNDAS RESIDÊNCIAS NO NORDESTE BRASILEIRO - Assis, Lenilton Francisco de (Programa de Pós-Graduação de Geografia Humana e Programa de Pós-Graduação de Geografia Física, 2009)
The article presents a preliminary analysis on the old and new uses of second homes in northeastern of Brazil. Used territory and multiterritoriality form the theoretical basis for this analysis that reviews some ontological and epistemological approaches to justify the employment of these categories/concepts in Geography.